The Impact of Strategic Intelligence on Marketing Agility: A Field Study in Private Universities in the Capital Municipality of Sana'a - Goaill, Majid Mapkhot Mapkhot; Al-Sabahi, Amal Salah Aldeen Ali (University of Science and Technology Journal for Management and Human Sciences, 2024)
This study aimed to determine the levels of marketing agility and strategic intelligence, as well as the impact of strategic intelligence on marketing agility in private universities in the Capital Municipality of Sana'a. The study adopted a descriptive-analytical approach and used a questionnaire as a tool for data collection from private universities that have been established for more than 15 years and have more than 20 educational programs. One hundred and thirty-seven questionnaires were distributed to university rectors, vice rectors, general secretaries, deans of colleges, marketing managers, heads of academic departments, registrars, and student affairs. A total of 118 valid questionnaires were collected for analysis. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data. The study found that the level of strategic intelligence practice in private universities was high, with the future vision dimension being the most practiced, while motivation was the least practiced. The level of marketing agility application was also high, with implementation agility being the most applied dimension, while participation agility was the least applied. The results also showed a significant statistical impact of strategic intelligence on marketing agility. The motivation and partnership dimensions of strategic intelligence had the greatest impact on marketing agility, while systematic thinking had the least impact. The study recommends increasing focus and attention on the motivation and partnership dimensions, as they have the greatest impact on marketing agility and increase the achievement of marketing agility in the face of increasing competition in the private university sector in Yemen.
Keywords: Strategic intelligence; marketing agility; private universities